Socialization and Training at Gloria Muda Volleyball Club - Edi Irwanto; Danang Ari Santoso; Bayu Septa Martaviano Triaiditya; Marki Sandi; Dadang Mubin (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2021)
The purpose of this service is to provide socialization and training at Gloria Muda Tambakrejo volleyball club, Bulurejo Village, Purwoharjo District, Banyuwangi Regency. The method used in this service is discussion and direct training (demonstration and practice) to the coaches and volleyball players of Gloria Muda Tambakrejo. The result of this activity was that the volleyball club coach Gloria Muda Tambakrejo gained new insights regarding the training program and how to train and was able to develop a training program that could be used to develop the technique and game of the Tambakrejo volleyball club. Young Gloria club players get training programmed according to the training program that suits their needs. Increased basic technical skills of passing, smash and vertical jump height of club players Gloria Muda Tambakrejo. Increased skills of passing and smash techniques and physical conditions (vertical jump) by 6.17%. For the basic technique of passing, there was an increase of 9, 53%. For the basic smash technique there is an increase of 3.20%. For the ability to vertical jump there is an increase of 3, 87%.